Inefficiency of the criminalization of physical aggressions against women or members of the family group in Tacna Judicial District - 2017. - Muguerza Casas, Ivette Aracelli (2020)
The present investigation work was carried out with the purpose of determining to what extent the criminalization of physical aggressions against women or members of the family group, in article 122-B of the Criminal Code, would be ineffective, in the judicial district of Tacna, Year 2017. The criminalization of physical aggressions against women or members of the family group, in article 122-B of the Criminal Code, is ineffective to a large extent, because contrasted with reality, instead of avoiding their commission and strengthening the principle of family unity, generates family disintegration and unprotection of the victim, in the judicial district of Tacna, 2017. The work corresponds to an investigation, legal, non-experimental cross-sectional partner. For this purpose, the information obtained through the application of the Questionnaires addressed to magistrates and lawyers was considered, as well as that obtained through the Document Review Guide applied to the judicial proceedings concluded for the crime of aggressions against women or group members. family, of the year 2017. The intimidating effect of the criminalization of physical aggressions against women or members of the family group, provided for in article 122-B of the Criminal Code, is ineffective to a great extent, to deter their commission and strengthen the maintenance of family and social order, thus generating disintegration of the family and unprotection of the victim; and the sentence of imprisonment for the crime of physical aggressions against women or members of the family group, provided for in article 122-B of the Criminal Code, is ineffective to a great extent, to comply with the resocializing effect of the penalty.